Combined Analysis of Volatile Terpenoid Metabolism and Transcriptome Reveals Transcription Factors Related to Terpene Synthase in Two Cultivars of Dendrobium officinale Flowers - Li, Ninghong; Dong, Yingxue; Lv, Min; Qian, Li; Sun, Xu; Liu, Lin; Cai, Yongping; Fan, Honghong (Frontiers in Genetics, 2021)
Dendrobium officinale is a kind of traditional Chinese herbal medicine. Its flowers could be used as health care tea for its aroma flavor and medicinal value. Most recent studies demonstrated the terpenoids are the main compoments of the aromatic sompounds in the flowers, but the biosynthesis of terpenoids is poorly understood in D. officinale. In the experiment, the flowers from two cultivars of D. officinale with different smell were collected. The transcriptome analysis and combined the volatile terpenoids determination were performed to identify the genes related to the biosynthesis of the terpenoids. The results showed that the different products of volatile terpenoids are α-thujene, linalool, α-terpineol, α-phellandrene, γ-muurolene, α-patchoulene and δ-elemene in two cultivars flowers. The transcriptome analysis totally detected 25,484 genes in the flowers. And 5340 differentially expressed genes were identified between two cultivars. Of these genes, 254 genes were mapped to terpenoid metabolism pathway. Among these gene, 13 TPS genes may have correlations with AP2/ERF, WRKY, MYB, bHLH and bZIP transcription factors by WGCNA analysis. The transcription factors have regulatory effects on TPS genes. These results may provide ideas for the terpenoid biosynthesis and regulatory network of D. officinale flowers.